143k views
24 votes
Solve for x, 2-x= -6-4x
a . -2/3
b.-2/5
c-8/3
d.-8/5​

2 Answers

2 votes

Answer:

x = -8/3

Explanation:

Consolidate x terms on the right side:

2-x= -6-4x becomes 2-x + x = -6-4x + x, which in turn becomes:

2 = -6 - 3x, or 3x = -8. Then, dividing both sides by 3, we get x = -8/3

User Niklas
by
4.7k points
1 vote

Answer:

-8/3

Explanation:

2 - x = - 6 - 4x <-- Add 4x to the left side

2 + 3x = - 6 <-- Subtract 2 from the left side

3x = -8 <-- Divide 3 on both sides

x = -8/3

User Lambok Sianturi
by
4.9k points